2010
DOI: 10.1089/met.2009.0080
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Fat Tissue Thickness Correlates with Endothelial Dysfunction and Other Cardiovascular Risk Factors in Patients with Metabolic Syndrome

Abstract: Epicardial fat tissue may be a useful parameter in the assessment of patients with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 25 publications
2
52
0
3
Order By: Relevance
“…Epicardial fat seems to affect the endothelial function and increase sympathetic system activity by its paracrine effect. A recent study by Aydin et al (2010) reported that EFT correlated with endothelial dysfunction assessed by flow-mediated dilatation at the brachial artery in patients with MS. On the other hand, increased sympathetic activation and decreased vagal activity could markedly suppress endothelial function (Hijmering et al 2002;Huang et al 2004). Based on these data and our findings, cardiac autonomic dysfunction and associated-endothelial dysfunction may be suggested as mechanisms of EFT for increased CVD risk in MS patients.…”
Section: Discussionmentioning
confidence: 96%
“…Epicardial fat seems to affect the endothelial function and increase sympathetic system activity by its paracrine effect. A recent study by Aydin et al (2010) reported that EFT correlated with endothelial dysfunction assessed by flow-mediated dilatation at the brachial artery in patients with MS. On the other hand, increased sympathetic activation and decreased vagal activity could markedly suppress endothelial function (Hijmering et al 2002;Huang et al 2004). Based on these data and our findings, cardiac autonomic dysfunction and associated-endothelial dysfunction may be suggested as mechanisms of EFT for increased CVD risk in MS patients.…”
Section: Discussionmentioning
confidence: 96%
“…Epicardial fat seems to affect endothelial function and increase sympathetic system activity by paracrine influence. EAT related to endothelial dysfunction assessed by flow-mediated dilatation of the brachial artery, in patients with metabolic syndrome (MS) (Aydin et al 2010). Furthermore, increased sympathetic activation and decreased vagal activity may markedly suppress endothelial function (Hijmering et al 2002;Huang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…В одном из исследований у пациентов с МС (n=50) показатель тЭЖТ продемонстрировал взаимосвязь с индексом НОМА -IR, а также липидами плазмы, СРБ и фибриногеном [16].…”
Section: результаты и обсуждениеunclassified